2019
DOI: 10.1016/j.bcp.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Anticholestatic mechanisms of ursodeoxycholic acid in lipopolysaccharide-induced cholestasis

Abstract: Lipopolysaccharide (LPS) from Gram (-) bacteria induces inflammatory cholestasis by impairing the expression/localization of transporters involved in bile formation (e.g., Bsep, Mrp2). Therapeutic options for this disease are lacking. Ursodeoxycholic acid (UDCA) is the first choice therapy in cholestasis, but its anticholestatic efficacy in this hepatopathy remains to be evaluated. To asses it, male Wistar rats received UDCA for 5 days (25 mg/Kg/day, i.p.) with or without LPS, administered at 8 a.m. of the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 95 publications
1
12
0
Order By: Relevance
“…There was no effect for UDCA on either IL-1α or IL-4. This is consistent with the report of Razori et al (24) who found that attenuation in TNF-α and IL-6 cytokines in LPS treated rats was not statically significant. Also, Diamond et al (25) showed the lack of effect of UDCA in reducing the expression of cytokines.…”
Section: Discussionsupporting
confidence: 93%
“…There was no effect for UDCA on either IL-1α or IL-4. This is consistent with the report of Razori et al (24) who found that attenuation in TNF-α and IL-6 cytokines in LPS treated rats was not statically significant. Also, Diamond et al (25) showed the lack of effect of UDCA in reducing the expression of cytokines.…”
Section: Discussionsupporting
confidence: 93%
“…Currently, ursodeoxycholic acid (UDCA) and obeticholic acid (OCA) are the only drugs approved by the United States Food and Drug Administration for cholestasis (Cabrera, Arab, & Arrese, 2019). Early treatment can alleviate symptoms, improve liver enzyme abnormalities and reduce mortality in patients with primary biliary cirrhosis (PBC; Razori et al, 2019). However, UDCA is used for early PBC and one‐third of affected patients show no response to it.…”
Section: Introductionmentioning
confidence: 99%
“…Early treatment can alleviate symptoms, improve liver enzyme abnormalities and reduce mortality in patients with primary biliary cirrhosis (PBC; Razori et al, 2019). However, UDCA is used for early PBC and one-third of affected patients show no response to it.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work [10], we studied the anti-cholestatic effects of ursodeoxycholic acid (UDCA) in LPS-induced cholestasis, as it is the "first choice" therapeutic approach for most cholestatic hepatopathies. Since its beneficial effects were partial, we decided to evaluate spironolactone (SL) as a complementary anti-cholestatic agent, which could act via alternative pathways.…”
Section: Journal Pre-proofmentioning
confidence: 99%
“…The time-course of the changes in the biliary output of the exogenously administered Bsep and Mrp2 solutes TC [10] and DBSP [22], respectively, have been assessed to estimate in vivo the transport efficiency of these canalicular carriers. Despite uptake of these solutes may be affected by LPS treatment [23], this process is unlikely to significantly influence biliary excretion, because 1) canalicular transfer but not basolateral uptake is the rate-limiting step in the hepatic handling of cholephilic compounds [24], and 2) kinetic studies suggest that the ABC canalicular transporters work under Tm conditions [25], so that changes in intracellular levels due to impaired uptake should have negligible, if any effect on biliary excretion; this situation is unlikely…”
Section: Biliary Excretion Of Exogenous Mrp2 and Bsep Substratesmentioning
confidence: 99%